Impact of Financial Reporting Quality on the Implied Cost of Equity Capital: Evidence from the Malaysian Listed Firms - Othman, Radiah (Asian Journal of Business and Accounting, 2010)
This paper investigates the factors associated with firms’ financial reporting choices and their economic impact on the cost of equity capital for the Malaysian listed firms over the period of 2000-2007. We find that there is a negative association between financial reporting quality choice and the number of shareholders, industrial competition, capital intensity and leverage. We also find that firms choosing to provide financial information of higher quality enjoy a lower cost of equity capital using implied cost of equity capital estimates. These findings suggest that those firms in emerging markets which provide higher quality of financial reporting reduce information risk, and these firms also obtain significant economic benefits.